Comparative transcriptome analysis of genes and metabolic pathways involved in sporulation in Ganoderma lingzhi. Issue 3 (17th January 2022) - Cai, Manjun; Tan, Zengdong; Wu, Xiaoxian; Liang, Xiaowei; Liu, Yuanchao; Xie, Yizhen; Li, Xiangmin; Xiao, Chun; Gao, Xiong; Chen, Shaodan; Hu, Huiping; Wu, Qingping
Abstract: Over the past decades, Ganoderma lingzhi spores have received considerable attention as a great potential pharmaceutical resource. However, the genetic regulation of sporulation is not well understood. In this study, a comparative transcriptome analysis of the low-sporing HZ203 and high-sporing YW-1 was performed to characterize the mechanism underlying sporulation. A total of 917 differentially expressed genes were identified in HZ203 and 1, 450 differentially expressed genes in YW-1. Differentially expressed genes involved in sporulation were identified, which included HOP1, Mek1, MSH4, MSH5, and Spo5 in meiosis. Positive regulatory pathways of sporulation were proposed as 2 transcriptional factors had high connectivity with MSH4 and Spo5 . Furthermore, we found that the pathways associated with energy production were enriched in the high-sporing genotype, such as the glyoxylate and dicarboxylate metabolism, starch and sucrose metabolism. Finally, we performed a weighted gene coexpression network analysis and found that the hub genes of the module which exhibit strong positive relationship with the high-sporing phase purportedly participate in signal transduction, carbohydrate transport and metabolism. The dissection of differentially expressed genes during sporulation extends our knowledge about the genetic and molecular networks mediating spore morphogenesis and sheds light on the importance of energy source during sporulation.